Suprathel Dressing at Split Thickness Skin Graft Donor Site for Pain Control and Wound Healing - Lubna Cheema, Sobia Manzoor, Usman Khalid, Romaisa Shamim, Hashaam, Zahid Tayyab, Mustehsan Bashir, (Pakistan Journal of Medical & Health Sciences, 2022)
Back ground: Split thickness grafting is a routinely done procedure in treatment of burn and coverage of other wounds. These patients require management of both donor site and grafted area. Donor site wound may be more painful and distressing as compared to the patient´s skin grafted area and there may be additional scarring. Different types of dressing are used for healing of SSG donor area. Aim: To compare conventional dressing and Suprathel dressing at SSG donor site in terms of total consumption of analgesic medication and duration of wound healing. Methods: Randomized control trial was conducted in the Department of Plastic and Reconstructive Surgery/ Burn unit of Mayo Hospital over a period of 1 year (Dec 20 – Dec 21). A total of 64 patients of skin grafting were included. They were divided into 2 groups, Group A (32) treated with conventional paraffin medicated gauze and in Group B (32) Suprathel dressing was used on graft donor site. Patients pain score was calculated using NVAS (Numeric visual analogue score) and healing time was recorded in both groups. Results: Total of 64 patients were included in study with 32 in each group. There were 35(54.7%) males and 29(45.3%) females. Pain score in Group A was: ≤ 5 in 11 patients (34.4%) and ≥ 5 in 21(65.5%). In Group B≤ 5 in 22 patients (68.85%) and ≥5 in 10(31.2%). Healing time in Group A was: ≤ 14 days in 17 patients (53.15%) and ≥14 days in 15(46.8%). In Group B ≤14days in 25(78.1%)and ≥ days 14 in 7( 21.9%). There was significant difference between patient pain score (.005) and healing time (p.0.03) in comparison of suprathel dressing and paraffin medicated treated donor site Conclusion: Suprathel represents a reliable epidermal skin substitute having an impact on wound healing and wound pain on donor site for graft. It enhances wound healing and decreases dose of analgesia. Keywodrs: Graft Donor site, Suprathel, Pain score, wound healing.